1997
DOI: 10.1007/s003810050127
|View full text |Cite
|
Sign up to set email alerts
|

Primary intracranial neoplasms of infancy and early childhood

Abstract: We investigated the age-related location, gender distribution, and histology of 107 brain tumors in children under 4 years of age seen in our department between 1984 and 1997. The male-to-female ratio was 1.4 (62/45 cases) with a prevalence of supratentorial tumors (60/47 = 1.3); the main histological entity was astrocytoma (33.6%), followed by ependymoma (14.0%). In the 1st year of life 22 cerebral neoplasms became clinically apparent. A higher ratio for supratentorial tumors was revealed (17/5 = 3.4), but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 39 publications
11
58
0
4
Order By: Relevance
“…This could reflect a real increase in incidence or could be related to change in diagnostic procedures [4,5,6]. As previously reported by many authors [7,8,9,10,11,12], males seem to be more susceptible than females. The male to female ratio in our series was 1:1.2, just like in other published reports.…”
Section: Discussionsupporting
confidence: 51%
“…This could reflect a real increase in incidence or could be related to change in diagnostic procedures [4,5,6]. As previously reported by many authors [7,8,9,10,11,12], males seem to be more susceptible than females. The male to female ratio in our series was 1:1.2, just like in other published reports.…”
Section: Discussionsupporting
confidence: 51%
“…Isaacs in his review of 250 perinatal intracranial tumors reported the incidence of PNET to be around 13.2 % [6]. Rickert et al reported that PNET was the most common tumor in first year of life, astrocytoma and ependymoma were highest in first two years of life and astrocytomas were highest in first four years of life accounting for one-third of all tumors in their epidemiological survey [9]. Congenital PNETs are rare in fetal and perinatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Ependimomak, plexu koroideetako tumoreak, PNET eta teratomak % 11, % 11 eta % 7,7ko portzentajeak izan zituzten hurrenez hurren. Emaitza horiek bat datoz beste batzuek argitaratu dituztenekin (9). Harrigarria da plexu koroideetako tumoreak denen % 1,2 baino ez izatea, eta 4 teratoide rabdoide atipiko bakarrik daudela 195 tumoreen artean (2. taula).…”
Section: Eztabaidaunclassified